2017
DOI: 10.1017/s002531541600182x
|View full text |Cite
|
Sign up to set email alerts
|

Syllidae (Annelida) from the Boreal and sub-Arctic seas off Norway (North Sea, Norwegian Sea, Barents Sea)

Abstract: A collection of more than 1500 specimens of Syllidae (Annelida, Polychaeta) from sub-Arctic and Boreal regions along the coast of Norway has been studied. We report 32 species, two of them new to science, belonging to the generaSphaerosyllisClaparède, 1863 andSyllisSavigny in Lamarck, 1818, and 16 new to Norway.Sphaerosyllis tarqueisp. nov. is characterized by having long blades on its compound chaetae and the presence of glands inside the dorsal cirri.Syllis kassp. nov. was reported, figured and described by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Amblyosyllis finmarchica was considered to be a nomen dubium [132], but it was later [36, 133] recognised as valid based on material from Iceland and Norway, respectively. The present work confirms the validity of the species.…”
Section: Resultsmentioning
confidence: 99%
“…Amblyosyllis finmarchica was considered to be a nomen dubium [132], but it was later [36, 133] recognised as valid based on material from Iceland and Norway, respectively. The present work confirms the validity of the species.…”
Section: Resultsmentioning
confidence: 99%
“…can be easily distinguished from the remaining Mediterranean Erinaceusyllis based on their compound chaetae: Erinaceusyllis belizensis (Russell, 1989) and Erinaceusyllis cryptica (Ben-Eliahu, 1977) have bidentate blades (San Martín 2003), while Erinaceusyllis erinaceus (Claparède, 1863) has unidentate, distinctly shorter blades, with a less pronounced dorso-ventral gradation (Verdes et al 2013). Moreover, contrary to the new species, the species of Erinaceusyllis typically occur in shallow water environments (San Martín 2005;Ramos et al 2010;Lucas et al 2017), even if some abyssal species originally assigned to the genus Sphaerosyllis Claparède, 1863, as Sphaerosyllis ridgensis Blake & Hilbig, 1990, and Sphaerosyllis ruthae San Martín, 2004 could actually belong to Erinaceusyllis (G. San Martín, pers. comm.).…”
Section: Systematicsmentioning
confidence: 90%
“…On the other hand, Exogone longicirris Webster & Benedict, 1887 has been recently assigned to Parexogone, and closely resembles P. wolfi. The main differences are only a slightly lower number of proventricular cell rows (11-14 vs 15-21) and a less pronounced spinulation along the blade edge (Eliason 1962;Lucas et al 2017). The spinulation of compound chaetae, however, shows geographical variability, as the Brazilian specimens examined by Barroso et al (2017) show less pronounced spines than those reported in the original description (San Martín 1991), thus appearing closer to P. longicirris.…”
Section: Systematicsmentioning
confidence: 94%
“…It is a journal with an established reputation, international reach and a broad scope across the marine realm. In this issue there are papers from around the world, from the Barents Sea (Lucas et al ., 2018) to the southern Philippine Sea (Yu & Xu, 2018). They detail basic research on marine organisms from the microscopic Chatonella spp.…”
mentioning
confidence: 99%